1992
DOI: 10.1111/j.1365-2362.1992.tb01932.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon‐independent renal hyperaemia and hyperfiltration after an oral protein load in Child A liver cirrhosis

Abstract: The work was designed to study the effects of a meat meal on glomerular filtration rate (GFR), renal plasma flow (RPF), and plasma concentrations of glucagon, insulin, growth hormone, renin, aldosterone, total amino acids, and NH3 in healthy humans (H) as well as in patients with Child A liver cirrhosis (LC). The meat meal produced renal hyperaemia and hyperfiltration without changes in the filtration fraction. Fractional Na excretion in urine increased significantly after the meat meal only in LC. Hyperinsuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Changes in NO and cGMP plasma concentrations as [20,21] and Woitas et al [22]. However, other investigators have reported higher average GFR values in cirrhotic well as the urinary excretion values are summarized in table 2.…”
Section: Metabolites Of Nitric Oxidementioning
confidence: 93%
“…Changes in NO and cGMP plasma concentrations as [20,21] and Woitas et al [22]. However, other investigators have reported higher average GFR values in cirrhotic well as the urinary excretion values are summarized in table 2.…”
Section: Metabolites Of Nitric Oxidementioning
confidence: 93%
“…GFR was measured as the inulin clearance performed with the constant-infusion technique of Walser et al [25], as described else where [9,21], Participants were admitted one at a time to the hospi tal at 8.30 a.m. exactly on the morning when B3 was drawn, after an overnight fast. Each participant received 20 ml/kg BW of water.…”
Section: Measurement O F Gfrmentioning
confidence: 99%
“…At 10.00 a.m., after 90-min equilibration, three clearance periods were obtained from each subject, each of 30-min duration (Ci, C2, C3), which were subsequently averaged. Blood and urine were analyzed for inulin by spectrophotometry [25], as described [9,21]. Inulin clearance was calculated by the standard formula as expressed per 1.73 m2.…”
Section: Measurement O F Gfrmentioning
confidence: 99%
See 2 more Smart Citations